Digital Entrepreneurs' Strategic Responses to the Incomplete Global Policy Framework for Blockchain-Based Business - Šilenskytė, Aušrinė; Butkevičienė, Jurgita; Dhanaraj, Charles (Routledge, 2022)
Adopting blockchain is a strategic priority of many companies worldwide. However, utilization of this technology remains hindered by the diversity of policy responses and lack of a global policy framework. We investigated blockchain-based entrepreneurs in North America, Europe, and Asia and analyzed 12 reputable cases in the industry to discover how they implemented their strategies. We provide an overview of the global policy framework for blockchain-based businesses and identify four tactics that can be adopted by digital pioneers to thrive within the formal and informal institutional voids (IV). We contribute to the international business literature by exploring IV as a multilevel opportunity and by deepening the understanding of IV outside traditionally considered geographical boundaries.
Keywords: institutional voids; blockchain; strategic responses; formal and informal institutions; institutional braiding; fi=Strateginen johtaminen|en=Strategic Management|